Acridine-Based SNS–Ruthenium Pincer Complex-Catalyzed Borrowing Hydrogen-Mediated C–C Alkylation Reaction: Application to the Guerbet Reaction - Biswas, Nandita; Sharma, Rahul; Sardar, Bitan; Srimani, Dipankar (Synlett, 2022)
SNS-based ruthenium pincer catalysts were applied in a Guerbet condensation reaction of primary alcohols to give β-alkylated dimeric alcohols in good yields. The ability of these complexes to convert ethanol into butanol was also investigated. The work was then extended toward the C-alkylation of secondary alcohols with primary alcohols to give α-alkylated ketones. Several control experiments showed the involvement of borrowing hydrogen in the protocol.
Keywords: borrowing hydrogen reaction; ruthenium catalysis; alcohols; Guerbet reaction; ketones; butanol